PENGARUH BRAND AMBASSADOR DAN BRAND TRUST TERHADAP KEPUTUSAN PEMBELIAN SEPEDA MOTOR PADA PT. YAMAHA ALFA SCORPII NANGKA PEKANBARU - Fadli, Mashur; Simangunsong, Johannes Peterson (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
The purpose of this study is to determine the influence of brand ambassador and brand trust on motorcycle purchasing decisions at PT. Yamaha Alfa Scorpii Nangka Pekanbaru. This study is a quantitative study with a sample of 100 respondents. Data sources were obtained from secondary data and primary data. This study used a questionnaire as a data collection technique with a purposive sampling method, namely a technique for determining samples with certain considerations or characteristics. The analysis methods used in this study are validity test, reliability test, classic normality assumption test, classic multicollinearity assumption test, classic heteroscedasticity assumption test, multiple linear analysis, t test, F test and coefficient of determination analysis (R2). The results of this study are Brand Ambassador (X1) has a positive and significant effect on purchasing decisions (Y), Brand Trust (X2) has a positive and significant effect on purchasing decisions (Y), and Brand Ambassador and Brand Trust have a positive and significant effect on purchasing decisions. Keywords: Brand Ambassador, Brand Trust, Purchasing Decision Keywords: Brand Ambassador, Brand Trust, Keputusan Pembelian